Bimbingan Industri Kecil Pembuatan Detergent Cream - Kardjikun Kardjikun (Balai Besar Kimia dan Kemasan, 1987)
Cream detergent as a washer material which is generally used in Indonesia at the present. It can be produced by simple process and its materials is very easy to get in market, so that cream detergent can be produced by home industry. Quality cream detergent is decided by composition of its materials andprocess. For established home industry program, we exert to write this sectionwhich contain; Standard quality of detergent Composition of material Process.